Ecological Agriculture and Sustainable Adaptation to Climate Change: A Practical and Holistic Strategy for Indian Smallholders - Bargout, Remy (Consilience, 2014)
The largest demographic in India suffering from the adverse impacts of global climate change are small farmers. India’s rural population is approximately 800 million, with the majority being households dependent on small-scale agriculture. For these smallholders, facing a common rural reality of disempowerment and limited disposable household capital, the agro-ecological results of climate volatility will have catastrophic costs. In a single growing season, even moderate climate abnormalities in temperature regime or moisture regime have shown to disrupt farm agro-ecology and diminish harvests over time. Using a precautionary principle to identify sustainable adaptation solutions, ecological farming offers the most practical and holistic traits of resilience, particularly in the areas of soil, water, and biodiversity. When acknowledging ecological agriculture as an empowering adaptation strategy for smallholders, the evident sustainability of this approach is also apparent alongside key structural dynamics limiting its adoption.